IMPACT OF INCLUSION-BASED EDUCATIONAL PRACTICES ON PROMOTING MULTICULTURALISM AMONG STUDENTS IN RURAL AREAS OF COLOMBIA - Luis Fernando González Cuesta; Diana Carolina Audor Clavijo; Julio Cesar Angarita Mogollón (LÍNEA IMAGINARIA, 2025)
The general objective of this documentary research is to analyze the impact of inclusive educational practices on the promotion of multiculturalism in rural areas of Colombia. Therefore, it is based on the recognition that, despite pedagogical advances, normative regulations, and constitutional recognition of multiculturalism in the country, traditional pedagogical strategies that do not appropriately value diversity continue to be implemented in rural areas. Therefore, gaps persist in the implementation of pedagogical strategies that integrate cultural identity, especially those of historically marginalized ethnic groups. The methodology used was documentary research, based on the review, collection, classification, analysis, and interpretation of relevant written sources. This also allowed for the identification of key concepts such as inclusive education, multiculturalism, educational policies, and intercultural pedagogical strategies regarding cultural diversity in rural contexts. Finally, the findings show that several rural institutions continue to operate using homogeneous and traditional models that fail to fully recognize the linguistic richness and traditional, cultural, and social diversity of their environment. This, in turn, generates demotivation, exclusion, low self-esteem, and barriers to comprehensive learning. Therefore, it is necessary to transform pedagogical approaches and teaching strategies into inclusive practices, with the appropriate design of contextualized strategies that benefit the entire educational community and guarantee the comprehensive development of all students.